Revisiting the potential of carbonized grain to preserve biogenic 87Sr/86Sr signatures within the burial environment - Styring, A; Evans, J; Nitsch, E; Lee-Thorp, J; Bogaard, A (Wiley, 2018)
Strontium (Sr) isotope analysis of archaeological crops is a potential method of provenancing and identifying the movement of crops in the past, but there remains uncertainty about whether original 87Sr/86Sr values can be obtained from carbonized buried grains. We have determined that hydrochloric acid (HCl) leaching removes some, but not all, exogenous Sr from carbonized cereal grains buried in soil for up to one year. We conclude that while further work could refine the leaching method, Sr isotope analysis of archaeological cereal grains can distinguish crops sourced from outside a particular (e.g., local) area if it can be shown that leaching moves grain 87Sr/86Sr values significantly away from the expected Sr signature.